In the Shadow of Transitional Justice Cross-national Perspectives on the Transformative Potential of Remembrance - Elcheroth, Guy; de Mel, Neloufer (Europa Perspectives in Transitional Justice, 2022)
"This volume bridges two different research fields and the current debates within them. On the one hand, the transitional justice literature has been shaken by powerful calls to make the doctrine and practice of justice more transformative. On the other hand, collective memory studies now tend to look more closely at meaningful silences to make sense of what nations leave out when they remember their pasts. The book extends the scope of this heuristic approach to the different mechanisms that come under the umbrella of transitional justice, including legal prosecution, truth-seeking and reparations, alongside memorialisation. The 15 chapters included in the volume, written by expert scholars from diverse disciplinary and societal backgrounds, explore a range of practices intended to deal with the past, and how making the invisible visible again can make transitional justice - or indeed, any societal engagement with the past - more transformative. Seeking to combine contextual depth and comparative width, the book features two key case analyses - South Africa and Sri Lanka - alongside discussions of multiple cases, including such emblematic sites as Rwanda and Argentina, but also sites better known for resisting than for embracing international norms of transitional justice, such as Turkey or Côte d'Ivoire. The different contributions, grouped in themed sections, progressively explore the issues, actors and resources that are typically forgotten when societies celebrate their pasts rather than mourning their losses and, in doing so, open new possibilities to build more inclusive processes for addressing the present consequences of past injustice. "